2021
DOI: 10.1093/ehjci/jeab215
|View full text |Cite
|
Sign up to set email alerts
|

CAD-RADS may underestimate coronary plaque progression as detected by serial CT angiography

Abstract: Aims We wished to assess whether different clinical definitions of coronary artery disease (CAD) [segment stenosis and involvement score (SSS, SIS), Coronary Artery Disease—Reporting and Data System (CAD-RADS)] affect which patients are considered to progress and which risk factors affect progression. Methods and results We enrolled 115 subsequent patients (60.1 ± 9.6 years, 27% female) who underwent serial coronary computed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Coronary CT angiography (CCTA) is the primary imaging modality for the non-invasive anatomical assessment of coronary artery disease (1)(2)(3)(4)(5). CCTA provides an excellent visualization of atherosclerotic plaques and enables the characterization of certain coronary plaque types (2,(6)(7)(8)(9)(10). While macrocalcified plaques are considered to be relatively stable, low attenuation plaques, positive remodeling, the napkin ring sign, and spotty calcifications on CCTA have been associated with plaque instability (6, 7, 11).…”
Section: Introductionmentioning
confidence: 99%
“…Coronary CT angiography (CCTA) is the primary imaging modality for the non-invasive anatomical assessment of coronary artery disease (1)(2)(3)(4)(5). CCTA provides an excellent visualization of atherosclerotic plaques and enables the characterization of certain coronary plaque types (2,(6)(7)(8)(9)(10). While macrocalcified plaques are considered to be relatively stable, low attenuation plaques, positive remodeling, the napkin ring sign, and spotty calcifications on CCTA have been associated with plaque instability (6, 7, 11).…”
Section: Introductionmentioning
confidence: 99%
“…They often do not cause luminal narrowing; therefore, they may not be noticeable with ICA. Thus, CCTA plays a prominent role in their diagnosis 55 …”
Section: Evaluation Of Coronary Plaques and Stentsmentioning
confidence: 99%
“…In terms of follow up of patients with ICC, CAD-RADS classification may underestimate the progression of disease [16]. Szilveszter et al, in a cohort of 115 patients, evaluated the progression of CAD disease by analyzing the segment stenosis (SSS), segment involvement score (SIS) and CAD-RADS [16].…”
Section: Coronary Computed Tomography Angiographymentioning
confidence: 99%
“…In terms of follow up of patients with ICC, CAD-RADS classification may underestimate the progression of disease [16]. Szilveszter et al, in a cohort of 115 patients, evaluated the progression of CAD disease by analyzing the segment stenosis (SSS), segment involvement score (SIS) and CAD-RADS [16]. Data obtained from the analysis with different models showed that it was possible to observe the progression of disease in 53%, 29.6% and 28.7% based on SSS, SIS and CAD-RADS, respectively.…”
Section: Coronary Computed Tomography Angiographymentioning
confidence: 99%
See 1 more Smart Citation